Determinants Affecting Menopause at Kamboja Posyandu, Tambakmas Village, Indonesia - Tigor Maylani; Suparji Suparji; Astin Nur Hanifah; Agung Suharto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Background: Menopause generally occurs in women aged 45–55 years. Various factors influence the age of menopause, including the possibility of early onset (premature menopause). Menopause has a significant impact on women's quality of life, ranging from physical changes and psychological disturbances to an increased risk of degenerative diseases such as osteoporosis and heart disease. This study aims to analyze the determinants influencing menopause among women aged 40–60 years at the Kamboja Posyandu in Tambakmas Village. Methods: This is a quantitative study using an analytic survey approach with a cross-sectional design. The population consisted of 200 women aged 40–60 years at the Kamboja Posyandu, from which a sample of 134 women was selected using proportional simple random sampling. Independent variables included age, genetics, lifestyle, general health, medical interventions, and environmental exposure. The dependent variable was menopause status. Data were collected using an interview questionnaire and analyzed using multinomial logistic regression with a 95% confidence level and a significance threshold of α = 0.05. Results: The findings indicate that increasing age, a family history of early menopause, unhealthy lifestyle, medical interventions, and environmental exposure significantly increase the likelihood of experiencing menopause. Analysis showed that five out of the six independent variables—age, genetics, lifestyle, medical interventions, and environment—had a statistically significant influence on menopause (p < 0.05). General health did not show a significant association with menopause (p = 0.840). Conclusion: The study concludes that the occurrence of menopause among women aged 40–60 years in the study area is influenced by a combination of age, genetic factors, lifestyle, medical interventions, and environmental conditions. These findings can serve as a basis for designing more targeted community-based intervention strategies, particularly in the form of menopause health education for healthcare workers and policymakers. The study is expected to serve as a reference to enhance women’s awareness and preparedness in facing the menopausal transition in a healthy and informed manner.